Understanding gastrointestinal cancer mortality disparities in a racially and geographically diverse population. (April 2022) - Nash, Rebecca; Russell, Maria C.; Miller-Kleinhenz, Jasmine M.; Collin, Lindsay J.; Ross-Driscoll, Katherine; Switchenko, Jeffrey M.; McCullough, Lauren E.
Abstract: Background: Gastrointestinal (GI) cancers represent a diverse group of diseases. We assessed differences in geographic and racial disparities in cancer-specific mortality across subtypes, overall and by patient characteristics, in a geographically and racially diverse US population. Methods: Clinical, sociodemographic, and treatment characteristics for patients diagnosed during 2009–2014 with colorectal cancer (CRC), pancreatic cancer, hepatocellular carcinoma (HCC), or gastric cancer in Georgia were obtained from the Surveillance, Epidemiology, and End Results Program database. Patients were classified by geography (rural or urban county) and race and followed for cancer-specific death. Multivariable Cox proportional hazards models were used to calculate stratified hazard ratios (HR) and 95% confidence intervals (CIs) for associations between geography or race and cancer-specific mortality. Results: Overall, 77% of the study population resided in urban counties and 33% were non-Hispanic Black (NHB). For all subtypes, NHB patients were more likely to reside in urban counties than non-Hispanic White patients. Residing in a rural county was associated with an overall increased hazard of cancer-specific mortality for HCC (HR = 1.15, 95% CI = 1.02–1.31), pancreatic (HR = 1.11, 95% CI = 1.03–1.19), and gastric cancer (HR = 1.17, 95% CI = 1.03–1.32) but near-null for CRC. Overall racial disparities were observed for CRC (HR = 1.18, 95% CI = 1.11–1.25) and HCC (HR = 1.12, 95% CI = 1.01–1.24). Geographic disparities were most pronounced among HCC patients receiving surgery. Racial disparities were pronounced among CRC patients receiving any treatment. Conclusion: Geographic disparities were observed for the rarer GI cancer subtypes, and racial disparities were pronounced for CRC. Treatment factors appear to largely drive both disparities. Highlights: Disparities in gastrointestinal (GI) cancer mortality vary by cancer type. Geographic disparities are more pronounced for rarer cancer types. Racial disparities are greatest for colorectal cancer (CRC), the most common GI cancer. Patient factors associated with mortality disparities vary by cancer type and disparity. Racial disparities in CRC mortality persist even among patients receiving treatment.